2006
DOI: 10.1186/1472-6823-6-1
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic assessment of subclinical left ventricular eccentric hypertrophy in adult-onset GHD patients by geometric remodeling: an observational case-control study

Abstract: Background: Most patients with growth hormone deficiency (GHD) show high body mass index. Overweight subjects, but GHD patients, were demonstrated to have high left ventricular mass index (LVMi) and abnormal LV geometric remodeling. We sought to study these characteristics in a group of GHD patients, in an attempt to establish the BMI-independent role of GHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
2
3
0
Order By: Relevance
“…However, the data from the majority of studies derive from small populations of normal/slightly overweight patients, or with a childhood-onset GHD. Similarly to our findings, De Gregorio et al [ 32 ] observed that a subgroup of GHD patients had high LVMi and eccentric hypertrophy. This finding is typically observed in patients with obesity, and so we may speculate that ectopic adipose tissue accumulation is the first strong determinant of cardiovascular remodelling in these patients and that GHD may act as an additive factor for increasing cardiometabolic risk by acting on MS elements and exacerbating cardiac alterations.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…However, the data from the majority of studies derive from small populations of normal/slightly overweight patients, or with a childhood-onset GHD. Similarly to our findings, De Gregorio et al [ 32 ] observed that a subgroup of GHD patients had high LVMi and eccentric hypertrophy. This finding is typically observed in patients with obesity, and so we may speculate that ectopic adipose tissue accumulation is the first strong determinant of cardiovascular remodelling in these patients and that GHD may act as an additive factor for increasing cardiometabolic risk by acting on MS elements and exacerbating cardiac alterations.…”
Section: Discussionsupporting
confidence: 92%
“…The ectopic fat deposition was also evidenced by echocardiography as follows: we found a higher EFT in patients with GHD, similarly to other authors [ 32 ]. The EF is a metabolically active organ that generates a variety of bioactive molecules with inflammatory properties that could significantly affect cardiac function [ 33 , 34 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our baseline observations that patients with AGHD had lower exercise capacity without left ventricular systolic dysfunction are in accordance with previous studies. 13 , 34 – 37 Conversely, other researchers have reported a decreased LVM 14 , 16 , 17 , 20 , 38 and reduced ejection fraction on echocardiography 38 , 39 or radionuclide angiography 20 in patients with GHD. However, when CMR is used, 1 year of GH treatment did not influence cardiac mass or contractility.…”
Section: Discussionmentioning
confidence: 98%